The Study on The Level Of Workers Compliance With Safety and Health Requirement at The Forest City Construction Site. - ab aziz, norfarah izzati; Tami, Hannifah (Recent Trends in Civil Engineering and Built Environment, 2021)
The construction industry is a very well-known and very important industry in the field of employment to build development in Malaysia. In turn, the industry can generate economic progress in the country. The construction sector has been flooded by foreign workers to meet the needs of the workforce where it contributes to communication problems in the delivery of information and training related to safety at construction sites. For workers who do not get clear and adequate information and knowledge, it is difficult to determine the level of risk and danger in each job performed. In turn, this contributes to unsafe working conditions and the occurrence of accidents at construction sites. Among the causes of accidents on construction sites are caused by the workers own self that does not care about safety on construction sites. This study, it uses two methods of an online questionnaire and interview. The data and analysis of this study were conducted through a respondent which is project managers, site managers, safety and health officers, site engineers, safety and health supervisors’ site and site supervisors. Analysis of in this study a mean score. The results of the data show that many respondents stated that the aspects of worker safety and health worker compliance at the construction site are satisfactory. Therefore, hope that this study will contribute to the management of safety and can be expanded to other relevant agencies.